Pirate latitudes : a novel - Crichton, Michael, 1942-2008. (New York : Harper, 2009)
"Michael Crichton presents a story about pirates in the New World"--Provided by publisher.
Keywords: Pirates -- Fiction; Ship captains -- Fiction; Naval history, Modern -- 17th century -- Fiction; Jamaica -- Fiction; Caribbean Area -- Fiction; Sea stories; Adventure fiction